Mass transfer modulation during salting of PEF pre-treated salmon fillets - Ana De Aguiar Saldanha Pinheiro; Fabio D’Elia; Jessica Genovese; Silvia Tappi; Urszula Tylewicz; Pietro Rocculi (country:DNK, 2022)
Salting is one of the oldest and simplest methods of preserving large quantities of fish for long periods of time; it is often used by the industry in combination with other traditional processing techniques, such as smoking, drying and cooking. This results in safer products with a better sensory appearance, but the salting kinetics require long times for the salt to diffuse into the product and to work properly. Among existing emerging technologies, pulsed electric fields (PEF) are a non-thermal treatment that has been shown to be effective in increasing mass transfer in both plant and animal tissues, without affecting the nutritional value, flavour, colour and texture of products. The aim of the present study was to study the application of PEF to Atlantic salmon filets before subjecting them to dry salting in order to improve the process effectiveness. The experimental design included 5 salmon (Salmo salar) sample groups for each salting time (3 and 6 hours): control (NT) and 4 types of PEF pre-treatment (PEF1, PEF2, PEF3, PEF 4). At the end of the salting times, the samples were rinsed in running water, dried and then subjected to the following analytical determinations: weight change, water activity, NaCl content change, water content change, texture, colour and the level of thiobarbituric acid reactive substances (tBars). The results shown that pulsed electric fields of 0.64 kV/cm (detected by PEF3), applied prior to the 3-hour salting of salmon, promote the diffusion of salt into the tissues, leading to increased NaCl retention by the muscle, thanks to the PEF permeabilization effect on cell membranes. These process parameters in fact generated a reversible electroporation capable of favoring a more homogeneous distribution of salt within the product, also allowing for a lower percentage weight variation compared to untreated samples. PEF did not provide any advantages in terms of reducing the water activity of the samples, especially during the shorter salting times, but it did improve the water ...